2002
DOI: 10.1149/1.1516773
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Alumina Refractory Corrosion by Sodium or Potassium Hydroxide in Glass Melting Furnaces

Abstract: In this paper the high-temperature corrosion of Al 2 O 3 refractories by MOH͑g͒ (M ϭ Na, K) found in the combustion atmospheres of typical air-and oxygen-fired glass-melting furnaces is examined using thermodynamic equilibrium calculations. These hydroxide species are considered to be the primary reactive alkali species since their partial pressures are significantly larger than those of M͑g͒, the next most abundant gas-phase alkali-containing species expected in typical furnace atmospheres. Thermochemical sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 15 publications
2
11
0
1
Order By: Relevance
“…It has also been shown that in spite of its simplicity, the associate species model can accurately predict the activities of components in metastable glass phases 4,5 . The databases developed using the associate species approach have found utility in waste glass modeling 4,5,8 and in understanding corrosion in refractories 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that in spite of its simplicity, the associate species model can accurately predict the activities of components in metastable glass phases 4,5 . The databases developed using the associate species approach have found utility in waste glass modeling 4,5,8 and in understanding corrosion in refractories 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…[34,35]. Korund eignet sich insbesondere aufgrund seiner guten Stabilität gegen Alkaliangriff für die Vergasung von Biomasse [36]. Auch in der Literatur hat sich der erfolgreiche Einsatz von korund-und mullitbasierten Filterkerzen bestätigt [37 -39].…”
Section: Steineunclassified
“…Hence, the refractory materials that are in contact with glass at elevated temperatures must have excellent chemical and mechanical stability [2]. Alumina is one of the most important refractory materials in glass furnaces due to its high melting point, good mechanical properties such as high hardness, high compressive strength, high elastic modulus and, good chemical and thermal stability [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%